The comparative archaeology of complex societies - Smith, Michael Ernest, 1953- (Cambridge University Press, 2012)
"Eleven leading archeologists describe their research on ancient empires, states, and chiefdoms using a comparative perspective. By making comparisons among sites, regions, and artifacts, these scholars produce new understanding of diverse specific cases, from the towering ruins of Angkor to the houses of Inca peasants. The reader learns about the political strategies of kings and chiefs, the daily choices of ordinary households, and the creative ways in which ancient peoples built their cities and shaped their landscapes. In the process, these chapters illustrate how to do comparative analysis using archeological data"--